Genomic diversity and metabolic potential of marine Pseudomonadaceae - Girard, Léa; Lood, Cédric; De Mot, René; van Noort, Vera; Baudart, Julia (Frontiers in Microbiology, 2023)
Recent changes in the taxonomy of the Pseudomonadaceae family have led to the delineation of three new genera (Atopomonas, Halopseudomonas and Stutzerimonas). However, the genus Pseudomonas remains the most densely populated and displays a broad genetic diversity. Pseudomonas are able to produce a wide variety of secondary metabolites which drives important ecological functions and have a great impact in sustaining their lifestyles. While soilborne Pseudomonas are constantly examined, we currently lack studies aiming to explore the genetic diversity and metabolic potential of marine Pseudomonas spp.. In this study, 23 Pseudomonas strains were co-isolated with Vibrio strains from three marine microalgal cultures and rpoD-based phylogeny allowed their assignment to the Pseudomonas oleovorans group (Pseudomonas chengduensis, Pseudomonas toyotomiensis and one new species). We combined whole genome sequencing on three selected strains with an inventory of marine Pseudomonas genomes to assess their phylogenetic assignations and explore their metabolic potential. Our results revealed that most strains are incorrectly assigned at the species level and half of them do not belong to the genus Pseudomonas but instead to the genera Halopseudomonas or Stutzerimonas. We highlight the presence of 26 new species (Halopseudomonas (n=5), Stutzerimonas (n=7) and Pseudomonas (n=14)) and describe one new species, Pseudomonas chaetocerotis sp. nov. (type strain 536T = LMG 31766T = DSM 111343T). We used genome mining to identify numerous BGCs coding for the production of diverse known metabolites (i.e., osmoprotectants, photoprotectants, quorum sensing molecules, siderophores, cyclic lipopeptides) but also unknown metabolites (e.g ARE, hybrid ARE-DAR, siderophores, orphan NRPS gene clusters) awaiting chemical characterization. Finally, this study underlines that marine environments host a huge diversity of Pseudomonadaceae that can drive the discovery of new secondary metabolites.